The Vogue of Fashion: Specifics of Development of Fashion-journalism in Russia - Радионцева, Екатерина Сергеевна (Philology & Human, 2019)
The article examines the typological features of one of the most stable segments of the Russian media industry – fashion-media. The analysis is based on empirical data-open information about fashion-media and publishing houses that produce them. The generally recognized typological division of the media into printed, audiovisual and electronic resources is applied as methodological basis, as well as such typological dominants as the audience and goals of publications are recognised. The author proposes to introduce another criterion into the typology in relation to public media, which will allow to designate the typological diversity of the media about fashion-these are the values broadcast and formed by publications. The article presents a new structure of fashion media, correlating with a stable classification in the fashion industry: publications on of Haute couture, pret-a-porter and mass market. The author mentions the most striking TV projects about fashion on public and specialized TV channels. The material can be useful not only for journalists, but also for practitioners of the fashion industry.